STUDY PENJADWALAN WAKTU PELAKSANAAN PADA PROYEK PELITA 4 TEMBUS PELITA 6 JL. BENDUNGAN KEL. SAMBUTAN KEC. SAMBUTAN - EDY SUBANGKIT, SIPUTRA (KURVA S JURNAL MAHASISWA, 2014)
Along with the development of the city of Samarinda, begin with the progress of the development of means of transport, especially the densely populated village, located on Jl. Bendungan 4 translucent Pelita Pelita 6 that many residents who require adequate road access, the level of difficulty to manage and run a highway project tinggi.Semakin increasingly higher degree of difficulty, meaning the longer the duration required for completing the project work.Therefore here is necessary a time management (time Management of) that in addition to sharpen priorities, also seek to improve the efficiency and effectiveness of the project pengelohan order to achieve maximum results from the resources available. All to achieve the goal of a highway project that meet the criteria of success are time (schedule) as well as the cost (budget) and quality (quality) and therefore the project Jl. Dam breaks Pelita Pelita 4 6 facilitate people around to start the routine day-to-day easier if the road project Pelita Pelita 6 4 breaks more easily bypassed by larger transport volume is.In addition to time management, would also be followed by the implementation of good projects and in accordance with the planning. With the management and implementation of a good time, then the risk of a highway construction project will be a little delayed. Directly it will reduce the swelling cost of the project, and will ultimately provide a distinct advantage for the project, and will ultimately provide a distinct advantage for the contractors in charge of project implementation.